2015
DOI: 10.3892/or.2015.3822
|View full text |Cite
|
Sign up to set email alerts
|

MCM2 is a therapeutic target of lovastatin in human non-small cell lung carcinomas

Abstract: Human non-small cell lung carcinoma (NSCLC) is one of the most common cancer worldwide. In previous studies, lovastatin, acting as an inhibitor of 3-hydroxy-3-methylglutaryl Co A (HMG-CoA) reductase, exhibited significant antitumor activity during tumorigenesis. However, whether or not this effect is mediated through changes in minichromosome maintenance (MCM) 2 expression remains unclear. The present study investigated whether lovastatin inhibits proliferation due to MCM2 in NSCLCs. We first assessed the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 33 publications
(35 reference statements)
1
46
0
Order By: Relevance
“…Lovastatin-treated animals showed significantly reduced MACC1 mRNA expression ( p < 0.05), confirming that the drug acts as a transcriptional inhibitor of MACC1 and thus inhibits MACC1-induced metastasis formation in vivo. In order to analyze further drug-induced effects, we determined the mRNA expression of genes that can be regulated by lovastatin (DNMT1, Col1A1, and MCM2) [3436]. DNMT1 and MCM2 showed no significant expression regulation upon treatment with lovastatin, whereas Col1A1 was significantly down-regulated, and HMGCR was significantly up-regulated (S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Lovastatin-treated animals showed significantly reduced MACC1 mRNA expression ( p < 0.05), confirming that the drug acts as a transcriptional inhibitor of MACC1 and thus inhibits MACC1-induced metastasis formation in vivo. In order to analyze further drug-induced effects, we determined the mRNA expression of genes that can be regulated by lovastatin (DNMT1, Col1A1, and MCM2) [3436]. DNMT1 and MCM2 showed no significant expression regulation upon treatment with lovastatin, whereas Col1A1 was significantly down-regulated, and HMGCR was significantly up-regulated (S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have provided cytological evidence for bioinformatics analysis that MCMs are involved in the progression of cell cycle pathways ( Figure 2). Knockdown of MCM2 reduced Rb, cyclinD1, cyclinA, and CDK4 expression and increased p53 and p21 expression, suggesting that by inducting the Cdk inhibitor p21cip14 and cyclin D/CDK4, downregulated MCM2 triggered the arrest of G1/S or G2/M [50,62]. Knockdown of MCM3 caused G1 arrest as evidenced by reduced expression of cyclinA [50].…”
Section: Effects Of Mcms In Cellular Signalingmentioning
confidence: 97%
“…The first strategy is to target MCM genes at transcriptional levels. It was shown that Trichostatin A, an HDAC inhibitor, and Lovastatin, an HMG-CoA reductase inhibitor, could downregulate MCM2 through activation of the JNK signaling pathway [60][61][62]. Also, Widdrol, an odorant compound, can activate DNA damage checkpoint through the signaling Chk2-p53-Cdc25A-p21-MCM4 pathway in HT29 cells [63].…”
Section: Mcms As Diagnostic Markers and Therapeutic Targetsmentioning
confidence: 99%
“…In addition, CCNB2 is key protein of the cyclin family and regulates the progression of the G2/M transition during the cell cycle (46). Furthermore, CCNB2, MAD2L1 and MCM2 are mitotic checkpoint associated proteins that are overexpressed in numerous types of human cancer (47)(48)(49). The dysregulation of mitotic checkpoints may also result in aneuploidy and the promotion of tumorigenesis (50).…”
Section: Discussionmentioning
confidence: 99%